Nephrocalcinosis: A Review of Monogenic Causes and Insights They Provide into This Heterogeneous Condition - Dickson, Fay J. (Int J Mol Sci, 2020)
The abnormal deposition of calcium within renal parenchyma, termed nephrocalcinosis, frequently occurs as a result of impaired renal calcium handling. It is closely associated with renal stone formation (nephrolithiasis) as elevated urinary calcium levels (hypercalciuria) are a key common pathological feature underlying these clinical presentations. Although monogenic causes of nephrocalcinosis and nephrolithiasis are rare, they account for a significant disease burden with many patients developing chronic or end-stage renal disease. Identifying underlying genetic mutations in hereditary cases of nephrocalcinosis has provided valuable insights into renal tubulopathies that include hypercalciuria within their varied phenotypes. Genotypes affecting other enzyme pathways, including vitamin D metabolism and hepatic glyoxylate metabolism, are also associated with nephrocalcinosis. As the availability of genetic testing becomes widespread, we cannot be imprecise in our approach to nephrocalcinosis. Monogenic causes of nephrocalcinosis account for a broad range of phenotypes. In cases such as Dent disease, supportive therapies are limited, and early renal replacement therapies are necessitated. In cases such as renal tubular acidosis, a good renal prognosis can be expected providing effective treatment is implemented. It is imperative we adopt a precision-medicine approach to ensure patients and their families receive prompt diagnosis, effective, tailored treatment and accurate prognostic information.